Discovery of potential inhibitors targeting the kinase domain of polynucleotide kinase/phosphatase (PNKP): Homology modeling, virtual screening based on multiple conformations, and molecular dynamics simulation. (October 2021) - Zhu, Jingyu; Zhang, Haoer; Jia, Lei; Ma, Lijun; Xu, Lei; Chen, Yun; Cai, Yanfei; Li, Huazhong; Huang, Gang; Jin, Jian
Graphical abstract: Highlights: The human PNKP protein was constructed by homology modeling and optimized through molecular dynamics simulation. A sequential high throughput virtual screening based on different docking modes was developed with the multiple MD-PNKP structures. The binding mechanism between the PNKP kinase domain and the inhibitor was revealed using MD simulation and binding free energy calculation. Abstract: In recent years, the level of interest has been increased in developing the DNA-repair inhibitors, to enhance the cytotoxic effects in the treatment of cancers. Polynucleotide kinase/phosphatase (PNKP) is a critical human DNA repair enzyme that repairs DNA strand breaks by catalyzing the restoration of 5'-phosphate and 3'-hydroxyl termini that are required for subsequent processing by DNA ligases and polymerases. PNKP is the only protein that repairs the 3′-hydroxyl group and 5′-phosphate group, which depicts PNKP as a potential therapeutic target. Besides, PNKP is the only DNA-repair enzyme that contains the 5′-kinase activity, therefore, targeting this kinase domain would motivate the development of novel PNKP-specific inhibitors. However, there are neither crystal structures of human PNKP nor the kinase inhibitors reported so far. Thus, in this present study, a sequential molecular docking-based virtual screening with multiple PNKP conformations integrating homology modeling, molecular dynamics simulation, and binding free energy calculation was developed to discover novel PNKP kinase inhibitors, and the top-scored molecule was finally submitted to molecular dynamics simulation to reveal the binding mechanism between the inhibitor and PNKP. Taken together, the current study could provide some guidance for the molecular docking based-virtual screening of novel PNKP kinase inhibitors.